Curative high‐dose reirradiation for patients with recurrent head and neck squamous cell carcinoma using IMRT or proton therapy: Outcomes and analysis of patterns of failure. Issue 11 (25th July 2022) - Beddok, Arnaud; Saint‐Martin, Caroline; Krhili, Samar; Eddine, Catherine Ala; Champion, Laurence; Chilles, Anne; Goudjil, Farid; Zefkili, Sofia; Amessis, Malika; Peurien, Dominique; Choussy, Olivier; le Tourneau, Christophe; et al.
Abstract: Purpose: To analyze outcomes of patients treated with curative reirradiation (reRT), with intensity‐modulated radiation therapy (IMRT) or proton therapy (PT) for recurrent head and neck squamous cell carcinoma (HNSCC). Materials: Among the 55 patients reirradiated for head and neck cancer from 30/08/2012 to 08/04/2019, 23 had HNSCC and received IMRT (52.2%) or PT (47.8%) at a median maximum dose to the CTV of 66 Gy. Results: After a median follow‐up of 41.3 months, 18 patients developed a locoregional recurrence (LR), of which eight (44.4%) occurred within the previously reirradiated volume. Two‐year locoregional failure‐free survival and overall survival were 18.3%[95%CI:7.1%–47.1%] and 42.5%[95%CI:26.2%–69.1%], respectively. Disease‐free survival was significantly longer in the PT group ( p = 0.031). Main late grade ≥2 toxicities were dysphagia and trismus. Conclusion: Curative reRT in HNSCC is possible for selected cases, but the LR rate in the irradiated field and the risk of toxicity grade ≥2 remain high.